Optimization of RAPD-PCR Conditions for the Study of Genetic Diversity of Centella asiatica - Devkota, Anjana; Bimb, Hari P; Bajracharya, Jwala; Jha, Pramod K (Nepal Journal of Science and Technology, 2012)
Random amplified polymorphic DNA (RAPD) is one of the molecular marker tools available for detecting the polymorphism in plant species. It has been used extensively for genetic diversity studies. In the present investigation, the RAPD reaction and cycling conditions were optimized for generating RAPD fingerprints of twenty one ecotypes of Centella. asiatica (L.) urban collected from different locations of Nepal. To determine the optimum conditions for PCR amplification, different concentrations of master mix ( 2X mix , Promega USA), template DNA, primer and PCR cycling conditions were varied. Reproducible amplified products were observed using 0.5 ?M of primer, 12.5?l master mix (2X), and 100 ng of template DNA in 25?l reaction volume of PCR. Cycling conditions were optimized with varying annealing temperature and initial denaturation temperature. The best cycling condition comprised of an initial denaturation of 3 min at 94°C, followed by 30 cycles of denaturation for 45 sec at 94°C, annealing for 1 min at 37°C, and extension for 1 min at 72°C and final extension at 72°C for 7 min . Of the 21 random primers tested, only 8 primers produced the best and reproducible amplification products. The optimized RAPD-PCR conditions and selected primers were subsequently used for the study of genetic diversity in C. asiatica. DOI: http://dx.doi.org/10.3126/njst.v12i0.6482 Nepal Journal of Science and Technology 12 (2011) 69-74